A review on vitamin B12 deficiency induced by metformin - Sireesha, Vankodoth; Sumaya; Pravarsha, Y.; Varun, Kompalli; Fatima, Faiqu; Sultana, Shafeen (International Journal Of Community Medicine And Public Health, 2024)
Multiple studies have established a higher prevalence of vitamin B12 deficiency in patients who have type 2 diabetes mellitus (T2DM). Metformin is prescribed as the 1st line oral glucose-lowering medication for individuals with T2DM. However, metformin therapy has been linked to vitamin B12 malabsorption, which can result in both biochemical and clinical manifestations of vitamin B12 deficiency. The long-term use of metformin is associated with a significant decrease in vitamin B12 levels, particularly in doses greater than 2000 mg per day over a period of 4 years. Vitamin B12 is a water-soluble vitamin. It acts as a cofactor for enzymes involved in DNA synthesis and neuroprotection at the cellular level. Hence, vitamin B12 deficiency can lead to various clinical consequences, including hematologic abnormalities such as megaloblastic anemia and hypersegmented neutrophil formation, peripheral neuropathy, and progressive axonal demyelination, hyperhomocysteinemia (HHcy). The latest "standards of medical care in diabetes-2017" issued by the American diabetes association recommends periodic assessment of B12 status and, if necessary, the use of B12 replacement therapy in diabetic patients taking metformin. In order to address the vitamin B12 deficiency associated with metformin several therapies are available including prophylactic supplements of calcium and vitamin B12, discontinuation of metformin, and replenishment of vitamin B12 stores through intramuscular or oral therapy. It is important to regularly monitor vitamin B12 levels for at least annually to prevent complications of vitamin B12 deficiency and continue with supplementation if metformin is still being used.